(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Field surveys were carried out at three locations in the centralclay plain of Sudan at Gedarif, Blue Nile and North Darfur States. Theobjective was to determine the most preferred resting sites of the duraandat, Agonoscelis pubescens , and other associated pentatomid species.These sites are where the chemical control campaigns of this pest areconducted every year. The results showed that A. pubescens preferredcertain types of trees as resting sites and that different pentatomid speciesaggregated and stayed together with it at these sites. A. pubescens wasthe main species sheltering on trees, while Carbula pedalis, anunconfirmed pest of sorghum, was the main species sheltering inmountain caves. Each of these two species seemed to join with a set ofspecific group of pentatomids, which differed from those associated withthe other. It is argued that control of C. pedalis may be unnecessary if it isproved that this insect is neither a pest of sorghum nor of any other maincrop.